Web – based support possibilities in sustainable urban development - Mickaityte, Aistė (Technological and Economic Development of Economy, 2004)
In the cause of world‐wide integration and on constant increase of the number of inhabitants in the cities that extend their territories, the urban development problems become a relevant issue. Sustainable urban development covers a number of activity fields ‐ sustainable planning of land handling, city renovation, sustainable buildings, rational power consumption, sustainable transport, distribution of pollution and shape of a city. The development of all the mentioned processes could be simplified by using information technologies that simplify and facilitate the work performed by specialists; improve its quality and results. Aims and principles of sustainable urban development, also the possibilities of usage of Internet medium ‐ calculators, software, and decision support system ‐ are defined in the presented article.Article in Lithuanian.Subalansuotos miestų plėtros internetinės paramos galimybėsFirst Published Online: 21 Oct 2010